2021
DOI: 10.1021/acs.jafc.1c02384
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide Suppresses High-Glucose-Induced Cardiomyocyte Apoptosis by Targeting Reactive Oxygen Species-Mediated Hypoxia-Inducible Factor-1α/Insulin-like Growth Factor Binding Protein 3 Activation

Abstract: It has been reported that 80% of diabetic patients die due to cardiovascular diseases. We previously demonstrated that activated hypoxia-inducible factor-1α (HIF-1 α)/insulin-like growth factor binding protein-3 (IGFBP-3) signaling by reactive oxygen species (ROS)-regulated prolyl hydroxylase domain-containing protein (PHD) is involved in high-glucose (HG)-induced cardiac apoptosis. Diallyl trisulfide (DATS), a garlic component, shows the strongest inhibitory effect on diabetic cardiomyopathy. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Some other studies have proposed regulation of this pathway by garlic-derived compounds and similar antioxidant phytochemicals [ 41 , 42 ]. Along these lines, allicin and diallyl trisulfide suppressed the HIF-1α pathway in cancer and other pathogenic contexts [ 3 , 4 , 7 , 13 , 30 ]. Thus, we propose the suppression of the HIF-1α pathway and the subsequent decrease in IRAK-M as the possible underlying cause of the differential/dual effects of TASE in monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies have proposed regulation of this pathway by garlic-derived compounds and similar antioxidant phytochemicals [ 41 , 42 ]. Along these lines, allicin and diallyl trisulfide suppressed the HIF-1α pathway in cancer and other pathogenic contexts [ 3 , 4 , 7 , 13 , 30 ]. Thus, we propose the suppression of the HIF-1α pathway and the subsequent decrease in IRAK-M as the possible underlying cause of the differential/dual effects of TASE in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with allicin has been shown to protect against the detrimental effects of nephropathy in a model of diabetes due to its antioxidant capacity and Nrf2 induction [ 6 ]. Moreover, this compound reduced reactive oxygen species (ROS) production in murine aortic endothelial cells that had undergone high glucose/hypoxia-induced injury [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diallyl trisulfide (DATS), an important oil-soluble organosulfur component and the most potent antioxidant in garlic oil, has been reported to inhibit the proliferation of various human cancer cells, including those originating from colon, lung, skin, and breast cancers ( Zhang et al, 2020 ). Modern pharmacological studies have claimed that DATS has antiinflammation and antioxidant properties ( Tsai et al, 2013 , Kuo et al, 2013 , Lin et al, 2021 ). A study of diabetic rats treated with garlic oil revealed that the activated PI3K/Akt/Nrf2-Keap1 signaling could alleviate cardiac oxidative stress ( Padiya et al, 2014 , Ou et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%